1989
DOI: 10.1016/0014-5793(89)81018-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing monoclonal antibody specific for α‐bungarotoxin: Preparation and characterization of the antibody, and localization of antigenic region of α‐bungarotoxin

Abstract: We prepared an a-bungarotoxin-specific monoclonal antibody that neutralizes the biological activity of the toxin in vivo. The antigenic determinant combining specifically with this antibody was determined on the basis of cross-reaction experiments using three other long neurotoxins and peptide fragments of a-bungarotoxin. The antigenic determinant was located on the peptide fragment containing S34-S35-R36-G37-K38, which forms a part of the expected site that binds to the acetylcholine receptor proteins Monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…An a-BT/antibody molar ratio of 1: 1.5 resulted in a < 2.5-fold increase for the time to death relative to control animals. A higher amount of NT-I mAb would probably be more efficacious since increased times to death of 4.3-and 13.5-fold were previously reported for an a-BT/mAb molar ratio of 1:1 and 1:5 respectively (Kase et al, 1989). Another study with N. n. atra cobrotoxin and various mAbs also reported prolonged times to death in mice administered toxin plus mAb .…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…An a-BT/antibody molar ratio of 1: 1.5 resulted in a < 2.5-fold increase for the time to death relative to control animals. A higher amount of NT-I mAb would probably be more efficacious since increased times to death of 4.3-and 13.5-fold were previously reported for an a-BT/mAb molar ratio of 1:1 and 1:5 respectively (Kase et al, 1989). Another study with N. n. atra cobrotoxin and various mAbs also reported prolonged times to death in mice administered toxin plus mAb .…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies with mAbs against x-BT reported that Ser34-Lys38 and Ser34-Glu4' represent neutralizing epitopes on the central loop (Chuang et al, 1989;Kase et al, 1989). In theory, antibodies which bind to a receptor-binding region of a snake post-synaptic neurotoxin with a higher affinity than the toxin-AchR complex (Kd 1 x I0-9-10-11 M) should have neutralizing potential (Weber and Changeux, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations